Development of wing pitch mechanism for robotic hummingbirds - Yong, Bryan Zhi Kiong (2018)
The hovering capabilities of Unmanned Aerial Vehicles (UAVs) has allowed them to be used in numerous applications from military reconnaissance to humanitarian aid. In the recent years, there has been a demand for smaller and quieter variants of such UAVs. This has opened a gateway for research on Micro Aerial Vehicles (MAVs), more specifically Flapping-Wing Micro Aerial Vehicles (FWMAVs). The key features of FWMAVs that mimicking birds and insects combine the capabilities of hovering flight, energy efficient lift production, and high manoeuvrability. Hovering however, remains a significant challenge in autonomous bio-mimicry flight as birds and insects have naturally unstable hovering flight with very complex stability control mechanisms and feedback loops.The objective of this paper is to develop a wing pitch mechanism for a robotic hummingbird FWMAV. The wing pitch mechanism should allow the study of how the wing pitch deflection affects the vector of thrust produced. A robotic hummingbird prototype is developed based on existing models developed in the Nanyang Technological University (NTU) Micro-Systems Laboratory, with the addition of an active wing pitch mechanism. The flapping mechanism and wing pitch mechanism design are detailed, together with the various tests performed using a force and torque sensor, coupled with a high-speed camera. The performance of the pitch control mechanism prototype will be demonstrated experimentally.